Review and Analysis of Book: Research Methodology in Simple Language - Morad Esmaeeli (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Undoubtedly, choosing a proper and suitable methodology for a research is regarded as one of the most fundamental principles of a scientific research. Familiarity and knowledge of these research methodologies and approaches will lead to the emergence of valuable and reliable studies.The book, Research Methodology in Simple Language, is written by Maryam Sadeghi. In her book, the author endeavored to clarify the methods and principles of writing a thesis for the students of Persian Literature.The author of the current article concentrates on surveying and reviewing this book. He also points to the weak and strong points of the book in question.  Based on findings of the article, despite the merits of the book such as dealing with research questions, containing specialized exercises, referring to the tables, and most importantly focusing on the field of Persian Literature, the book has many fundamental problems, including the contradiction between the title of the book and its content, the writer’s  lack of  attention to the basic rules of writing and editing, the presence of confusing sentences suffering from lack of enough information, and its incomprehensibility. These shortcomings will prevent its readers from not only its full understanding but also from benefitting from it.